Hydration of C3S and Al-doped C3S in the presence of gypsum - Neto, José da Silva Andrade; Rodríguez, Erick D.; Monteiro, Paulo J. M.; Gómez-de-la-Torre, María de los Ángeles; Kirchheim, Ana Paula (Elsevier, 2022)
A complete understanding of the effect of gypsum on the C3S hydration and the role of aluminum has not been achieved. The effects of gypsum (at 2.5 wt% and 5.0 wt%) on the hydration of tricalcium silicate (C3S) and aluminum-doped C3S (Al-C3S) hydration are assessed. Isothermal calorimetry, thermodynamic modeling, XRD, TGA, and 27Al and 29Si MAS-NMR were performed to analyze gypsum's influence on the hydration of C3S and Al- C3S. The inclusion of gypsum retarded the initial hydration (first 3 h) for both C3S and Al-C3S due to the interaction between the sulfate ions and C3S. In contrast, gypsum enhanced the hydration of both C3S and Al-C3S afterward. The removal of Al3+ ions of the pore solution by the formation of ettringite is not the mechanism behind the enhancement of C3S hydration by gypsum, which mainly results from changes in C-S-H morphology and increases in the ionic strength.
Keywords: Cemento; Sulfatos; Yeso; Cement hydration; Doped alite; Sulfate; Alite